Utilization of Natural Polymer Wall Materials in Strategies for Health-Effective Lycopene Encapsulation - Huadong, Yotsinee; Foophow, Tita; Sukonket, Thitinat; Phoohinkong, Weerachon (Journal of Food Health and Bioenvironmental Science, 2023)
Natural phytochemical carotenoids, pivotal for human health, enhance wellness, and exhibits anti-aging properties. Lycopene, distinguished by exceptional antioxidant properties, offers protection against oxidative stress. Studied extensively for its potential in medical interventions, it mitigates the risk of diseases like arteriosclerosis and breast cancer. However, lycopene’s high antioxidant activity makes it prone to degradation from environmental stresses like oxygen and light, impacting processing and storage. Its water and ethanol insolubility contribute to poor bioavailability. Encapsulation technology addresses these challenges, gaining interest for health benefits in functional foods and cosmeceutical products. The process of lycopene encapsulation, with a specific focus on the selection of diverse wall materials, has demonstrated a substantial impact on both the physical and functional attributes of the encapsulated lycopene within natural biomaterials employed for biomedicine. Natural polymers assume a crucial role in the advancement of biomedicine, nutraceuticals and the functional food industry, particularly in the encapsulation of natural active compounds such as lycopene. Consequently, there is a discernible trend towards the extensive utilization of natural polymers. The choice of a suitable wall material is of paramount importance as it significantly determines the efficacy and success of the encapsulation process. The utilization of natural polymer wall materials presents potential strategies for health-effective lycopene encapsulation. This paper provides a comprehensive overview of lycopene encapsulation, specifically focusing on polysaccharides and proteins, including oligosaccharides and cyclodextrin. The incorporation of these natural polymers in lycopene encapsulation enhances the bioavailability and stability of lycopene, rendering it suitable for diverse biomedical and nutritional applications.